URBAN STRUCTURE AND SUSTAINABLE URBAN TRANSPORT - Mehdi Moeinaddini, author 605327; Zohreh Asadi-Shekari, author; Zahid Sultan, author; Muhammad Zaly Shah, author 606189; Amran Hamzah, author 615118; Hishamuddin Jamaluddin, editor 617806 (Johor Bahru, Johor : Penerbit UTM Press, 2017)
Includes bibliographical references and index